THEORETICAL FOUNDATIONS OF INTERDISCIPLINARY INTEGRATION FOR DEVELOPING TOURISM-RELATED CONCEPTS: A CASE STUDY OF THE SUBJECTS "THE WORLD AROUND US," "ETIQUETTE," AND "FUTURE STUDIES - Dilorom Khotam qizi Ismatova (International Journal of Literature and Language Studies, 2026)
The development of tourism-related concepts among primary school students requires an interdisciplinary approach that integrates knowledge, skills, and values across different subjects. This study examines the theoretical foundations of interdisciplinary integration in developing tourism-related concepts through the subjects The World Around Us, Etiquette, and Future Studies. The research explores how these subjects contribute to students' understanding of cultural heritage, natural resources, environmental protection, social responsibility, and sustainable tourism. A qualitative research approach was employed using curriculum analysis, classroom observation, and the review of pedagogical literature. The findings indicate that interdisciplinary integration enhances students' cognitive development by connecting theoretical knowledge with practical experiences.